Influence of location, elevation gradients, processing methods, and soil quality on the physical and cup quality of coffee in the Kafa Biosphere Reserve of SW Ethiopia - Tassew, A.A.; Yadessa, G.B.; Bote, A.D.; Kufa Obso, T. (Elsevier, 2021)
In-depth forest coffee cup quality assessments have not been conducted yet on Kafa Biosphere Reserve coffees. Hence, the influence of location, elevation gradient, and processing methods on coffee bean physical and sensorial qualities, and the relationship between soil and coffee quality variables were studied in 2017. Districts (Gimbo, Gawata, and Decha), elevation gradient ranges (low-<1600, mid-1600-1800, and high->1800 m a.s.l), and processing methods (wet, semi-wet, and dry) were taken as factors. Preliminary coffee quality assessment data was collected from cup quality analysis of coffee beans obtained from the combination of the three factors where four replicate samples were taken for each of the combinations. The effect of location was only significant for bean moisture content and there was no significant (P > 0.05) difference among locations for above 14 screen retention and preliminary cup quality variables (odor, raw, acidity, body, flavor, cup, total, and grade). The elevation gradient had a significant (P < 0.001) effect on the scores of above 14 screen retention and most of the cup quality variables, but not on moisture content and odor. The effect of the coffee processing method was not significant (P > 0.05) on most of the preliminary cup quality variables, but it was significant for moisture content (P < 0.001), odor (P < 0.05), and overall raw (P < 0.01) scores. Screen retention was decreased with increasing elevation gradient but with better quality. High elevation coffees processed with the dry method gave better raw (38.5–40 ​%) and cup (48.00–51.75 ​%) quality scores. Except for high soil molybdenum and clay percentage, reduced amounts of most of the soil nutrients, pH, and silt percentage were important for better forest coffee quality. Since each sampled forest had diverse shade types and densities, a further investigation that includes the component of shade is strongly recommended in future studies.